Polymer of intrinsic microporosity (PIM-1) enhances hydrogen peroxide production at Gii-Sens graphene foam electrodes - Maisa Azevedo Beluomini; Yu Wang; Lina Wang; Mariolino Carta; Neil B. McKeown; Simon M. Wikeley; Tony D. James; Pablo Lozano-Sanchez; Marco Caffio; Nelson Ramos Stradiotto; Maria Valnice Boldrin Zanoni; Frank Marken (Electrochemistry Communications, 2022)
3D-graphene foam electrodes (Gii-Sens) immersed in a phosphate buffer solution of pH 7 are shown to generate hydrogen peroxide at a significantly faster rate in the presence of a nanoparticulate polymer of intrinsic microporosity (PIM-1). The effect is demonstrated to be associated at least in part with oxygen binding into PIM-1 under triphasic conditions. The release of the oxygen at the electrode|solution interface quadruples H2O2 production. Generator–collector experiments are performed with a graphene foam disk generator and a platinum disk electrode collector to allow in situ detection of hydrogen peroxide and oxygen.